Geographical and host species barriers differentially affect generalist and specialist parasite community structure in a tropical sky-island archipelago. Issue 1904 (12th June 2019) - Gupta, Pooja; Vishnudas, C. K.; Ramakrishnan, Uma; Robin, V. V.; Dharmarajan, Guha
Abstract : Understanding why some parasites emerge in novel host communities while others do not has broad implications for human and wildlife health. In the case of haemosporidian blood parasites, epidemic wild bird mortalities on oceanic islands have been linked to Plasmodium spp., but not genera like Haemoproteus . Indeed, Haemoproteus is absent from many oceanic islands. By contrast, birds on continental islands share long coevolutionary histories with both Plasmodium and Haemoproteus, and are thus ideal model systems to elucidate eco-evolutionary endpoints associated with these parasites in oceanic islands. Here, we examine eco-evolutionary dynamics of avian haemosporidian in the Shola sky-island archipelago of the Western Ghats, India. Our analyses reveal that compared to Plasmodium, Haemoproteus lineages were highly host-specific and diversified via co-speciation with their hosts. We show that community structure of host-generalist Plasmodium was primarily driven by geographical factors (e.g. biogeographic barriers), while that of host-specialist Haemoproteus was driven by host species barriers (e.g. phylogenetic distance). Consequently, a few host species can harbour a high diversity of Plasmodium lineages which, in turn, are capable of infecting multiple host species. These two mechanisms can act in concert to increase the risk of introduction, establishment, and emergence of novel Plasmodium lineages in island systems.